Zdokonalení integrace SSSD a SUDO - Šrubař, Michal (Vysoké učení technické v Brně. Fakulta informačních technologií, 2015)
Cílem této bakalářské práce je zlepšení integrace mezi SUDO a SSSD se zaměřením na vylepšení podpory SUDO pravidel uložených na serveru FreeIPA. Zabývá se popisem LDAP SUDO provideru a prezentuje návrh a implementaci IPA SUDO providera. Navržený provider eliminuje nadbytečnou režii překládání SUDO pravidel z IPA SUDO schématu do nativního LDAP SUDO schématu na straně FreeIPA serveru.

The purpose of this thesis is to improve integration between SUDO and SSSD with a fo- cus on improved support of SUDO rules stored on an FreeIPA server in the native IPA SUDO scheme. It presents documentation of LDAP SUDO provider and also the design and implementation of a native IPA SUDO provider. The designed provider eliminates an unnecessary overhead of exporting SUDO rules from IPA SUDO schema to native LDAP SUDO scheme on an FreeIPA server.
Improved Integration of SSSD and SUDO
Keywords: SUDO; nativní LDAP SUDO schéma; IPA SUDO schéma; FreeIPA; SSSD; LDAP SUDO provider; IPA SUDO provider; SUDO; native LDAP SUDO schema; IPA SUDO schema; FreeIPA; SSSD; LDAP SUDO Provider; IPA SUDO Provider